Touching art : the poetics and the politics of exhibiting the Tree of Life - Fonseca, Maria Emília (Cambridge Scholars, 2011)
This study focusses on the exhibition of the Tree of Life, a sculpture made in Mozambique of decommissioned, dismantled weapons, created to celebrate peace and commissioned by the British Museum, chosen to be the symbol of the 'Africa 2005' season of cult.